The Effect of Financial Performance and Dividend Policy on the Firm Value of Food and Beverage Companies Listed on the Indonesia Stock Exchange: The Moderating Role of CSR - Theresa Diaz Maharani; Augustina Kurniasih (Universitas Mercu Buana, 2026)
The value of a firm is a crucial factor taken into account by investors when making investment choices. The food and beverage sector has seen swift expansion, including in Indonesia, and has made the most significant contribution to non-oil and gas industrial GDP, along with national GDP, in comparison to other non-oil industries. Nevertheless, the market value of food and beverage firms on the Indonesia Stock Exchange has decreased lately. Consequently, it is essential to analyze the elements that affect the decline in company value. This research is empirically investigate how financial performance and dividend policy influence firm value, and using corporate social responsibility (CSR) disclosure as a moderating factor. The population for the study is food and beverage firms that are listed on the Indonesia Stock Exchange in 2024. The sample was chosen utilizing a purposive sampling technique according to established criteria. Data were examined through Moderated Regression Analysis (MRA). The findings show that financial performance positively and significantly impacts firm value, meanwhile dividend policy and CSR disclosure negatively and significantly affect firm value. Moreover, CSR disclosure diminishes the impact of financial performance and dividend policy on the value of the firm. The results suggest that food and beverage firms must align profitability, dividend policies, and CSR initiatives to create a more sustainable corporate value approach